A Conceptual Framework to Enable the Changes Required for a One-Planet Future. (1st October 2015) - Honig, Maria; Petersen, Samantha; Herbstein, Tom; Roux, Saul; Nel, Deon; Shearing, Clifford
Abstract : We conceptualise a framework that incorporates psychological and non-psychological factors influencing pro-environmental behaviour. We conducted qualitative investigations in five sectors in South Africa, where individuals and groups are dealing with significant environmental issues, including climate change, biodiversity loss and land-use change. We found three fundamental elements necessary for behavioural change to be realised: awareness (A) is defined as an understanding that society and earth systems are connected; motivation (M) involves the personal and operational drivers that encourage an individual or organisation to respond to new levels of awareness; and pathways (P) recognise the practical solutions and opportunities that facilitate actual change. AMP was built up from thirty-eight variables that cut across between three and five of the case studies, which were further grouped into fourteen categories. The inter-connectedness of AMP suggests that for pro-environmental behaviour to occur, attention cannot be focused on satisfying one of the elements in isolation. This is the first attempt to integrate theory from social psychology, sociology, organisational theory and management in a conceptual framework for pro-environmental behaviour. The AMP framework is useful for supporting practitioners or change-agents designing environmental sustainability initiatives.